High-pressure Treatment of DMAc/LiCl Swollen Softwood Pulp - Jasmina Obradovic; Pedro Fardim; Lippo Lassila; Patrick Navard; Dennis Kronlund (NORTH CAROLINA STATE UNIV DEPT WOOD & PAPER SCI, 2022)
Swollen softwood cellulose pulp in a DMAc/LiCl solvent system was compressed under elevated pressure (up to 900 MPa) in a Bridgman anvil press. The influence of high pressure on two cellulose systems was studied by measuring X-ray diffraction, mechanical and optical properties and observing scanning electron micrographs of the morphology. Compressed swollen cellulose, washed with distilled water, had lower elastic modulus and hardness compared to swollen cellulose washed with a combination of 2-propanol and deionized water. This work showed that material with lower mechanical properties will be affected more by compression and will result in higher mechanical properties after pressure treatment. Transmitted light in the visible range for both systems was increased after elevated pressure was applied. The XRD measurements revealed the decrease of the cellulose crystallinity after high pressure treatment for all swollen cellulose samples. The morphology of the compacted samples showed noticeable differences between the compact smooth surface and the layered core.